(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The sun plays an important role in our health, and too much sun exposure may cause anything from sunburns to skin cancer. Human skin cancer has become a growing health issue. Despite the fact that individuals are aware of the risks, skin damage caused by sunshine has risen in recent decades. The public nowadays relies on weather predictions to learn about UV radiation. For a certain broad region, the author offers rough or average predictions. To minimize the impacts of natural background radiation, this article provides a technique for calculating UV radiance utilizing UV sensors that detect the radiation and operate at a 300 nm wavelength. The sensor provides good detecting results at low and high UV levels, with response and regeneration durations of 22 seconds and 39 seconds, respectively. Using a Raspberry Pi and an LCD display, the author may also monitor and see the preventive steps that need to be performed.